The Model and Process of Buddha-Dhamma Communication through Social Media of Buddhist Monks in Thailand - Sirivathano (Loonnawan), Phra Thanit (Journal of International Buddhist Studies, 2015)
The Dhamma communication through the social networks in Thailand, it was found that, they have used as the Facebook, the YouTube and Dhamma website with uploaded pictures and videos about the religious practices as the Dhamma Talks and Dhamma Lectures both in Thailand and abroad. In addition, the Dhammapresentation with slide or posters were mostly made as simple and up to date with the current events. Regarding to the survey study, it was found that the model of Dhamma communication through the Facebook, YouTube and Dhamma official websites and the Dhamma contents were mostly presented by the slide pictures with the Buddha’s proverbs, quotations and poems. There were two models of the Dhamma Talk as: 1) the Dhamma contents that posted in the Timeline and 2) the DhammaTalk in multimedia and the Dhamma conversation. The Dhamma conversation was mostly used the multimedia on the answering of Dhamma Quiz. The focused groups have been made by the Buddhist monks, academic scholars and luminaries, it was found that 1) the model and process of Dhamma communication in Thailand must be modern, up to date, useful information, the contents and information are accurate and all information should be linked to other websites.